Analysis and theoretical modeling of 18O enriched carbon dioxide spectrum by CRDS near 1.35 μm: (II) 16O13C18O, 16O13C17O, 12C18O2, 17O12C18O, 12C17O2, 13C18O2 and 17O13C18O. (April 2017) - Karlovets, E.V.; Campargue, A.; Kassi, S.; Tashkun, S.A.; Perevalov, V.I.
Abstract: This contribution is the second part of the analysis of the room temperature absorption spectrum of 18 O enriched carbon dioxide by very high sensitivity Cavity Ring Down spectroscopy between 6977 and 7918 cm -1 (1.43–1.26 μm). Overall, more than 8600 lines belonging to 166 bands of eleven carbon dioxide isotopologues were rovibrationnally assigned. In a first part (Kassi et al. J Quant Spectrosc Radiat Transfer 187 (2017) 414–425, http://dx.doi.org/10.1016/j.jqsrt.2016.09.002 ), the results relative to mono-substituted isotopologues, 16 O 12 C 18 O, 16 O 12 C 17 O, 12 C 16 O2 and 13 C 16 O2, were presented. This second contribution is devoted to the multiply-substituted isotopologues or clumped isotopologues of particular importance in geochemistry: 16 O 13 C 18 O, 16 O 13 C 17 O, 12 C 18 O2, 17 O 12 C 18 O, 12 C 17 O2, 13 C 18 O2 and 17 O 13 C 18 O. On the basis of the predictions of effective Hamiltonian models, a total of 3195 transitions belonging to 73 bands were rovibrationnally assigned for these seven species. Among the 73 observed bands, 55 are newly reported. All the identified bands correspond to Δ P= 10 and 11 series of transitions, where P= 2V 1 +V 2 +3V 3 is the polyad number ( V i are vibrational quantum numbers). The accurate spectroscopic parameters of 70 bands have been determined from the standard band-by-band analysis. Global fits of the measured line intensities of the Δ P= 10 series of transitions of 17 O 12 C 18 O and 16 O 13 C 18 O and of the Δ P= 11 series of transitions of 12 C 18 O2, 17 O 12 C 18 O, 16 O 13 C 18 O and 13 C 18 O2 were performed to determine the corresponding sets of the effective dipole moment parameters. Highlights: Cavity Ring Down spectroscopy of 18 O enriched CO2 between 6977 and 7918 cm -1 . Analysis of the spectrum of the multiply-substituted or clumped-isotopologues. 73 bands are assigned to 16 O 13 C 18 O, 16 O 13 C 17 O, 12 C 18 O2, 17 O 12 C 18 O, 12 C 17 O2, 13 C 18 O2 and 17 O 13 C 18 O. 55 bands are newly reported. New effective dipole moment parameters for ∆ P =10–11 series of bands.